Numerical investigations of multiple cross-arm pre-tensioned cable stayed BRBs with pin-ended stays. (September 2018) - Zhou, Peng; Guo, Yan-Lin; Pi, Yong-Lin
Abstract: This paper proposes Multiple cross-arm Pre-tensioned Cable Stayed Buckling-Restrained Braces (MPCS-BRBs) with pinned connections between stays and external tube. By adopting pin-ended stays, the additional bending moment that would be exerted on those connections can be effectively released instead of fixed connections. This eliminates premature strength failures at those connections and simplifies the tensioning process of the cables, thus making the pin-ended stays to be a very practical option in engineering applications. Comparative studies have been conducted on the elastic buckling, load resistance and cyclic behaviors of the MPCS-BRBs with and without additional minor diagonal cables through Finite Element Analysis (FEA). Explicit expressions for the elastic buckling loads of the two types of MPCS-BRBs are obtained in closed form through curve fitting based on a generalized structural design parameter β of the external restraining system. It is found that the elastic buckling performance of the MPCS-BRBs with additional minor diagonal cables could be enhanced dramatically as compared to those not possessing the minor diagonal cables. At last, by ensuring the major cables not to become slack before reaching ultimate failures of the MPCS-BRBs, the load resistance and cyclic behaviors subjected respectively to monotonic and cyclic axial loads are explored through an elastic-plastic FEA. Corresponding lower limits of restraining ratios are attained, where they would provide fundamentals and guidance for preliminary design of the MPCS-BRBs in actual engineering applications. Highlights: MPCS-BRBs with pin-ended stays are proposed. Elastic buckling, load resistance and cyclic behaviors of MPCS-BRBs are studied. Explicit expressions for elastic buckling loads of MPCS-BRBs are obtained through curve fitting. Elastic buckling performance of MPCS-BRBs with minor diagonal cables is dramatically enhanced. Lower limits of restraining ratios are attained for MPCS-BRBs under either monotonic or cyclic axial loads.